Pay talk in contemporary workplaces - Denice, Patrick; Rosenfeld, Jake; Sun, Shengwei (Social forces, 2025)
Drawing on a unique survey of US workers with information about their employers’ policies on pay discussions and whether workers engage in such talk with their coworkers, we provide the most comprehensive investigation into pay talk in workplaces to date. Unlike existing treatments, we focus on core organizational and relational factors that influence whether workers talk about pay. We theorize pay talk as a challenge to managerial discretion, and we hypothesize that organizational attributes related to pay-setting influence workers’ willingness to discuss wages and salaries with colleagues. Managers, in turn, combat such challenges to their discretion by instituting pay secrecy rules. Particular relational factors within organizations are related to workers’ violations of these rules. Findings indicate that the likelihood of pay discussions varies by workplace pay secrecy rules, managerial relations within organizations, and, in certain model specifications, sector and career turning points. Among status characteristics, only age is associated with discussing pay, with younger workers significantly more likely to talk about pay and to violate organizational rules meant to suppress pay discussions.